مدوّنة المناقب في التُّراث الجزائري خلال القرن 19م - بركات, إسماعيل (جامعة الوادي - University of Eloued, 2017)
أشارت الأبحاث والدراسات العربية والأجنبية إلى أهمية كتب المناقب في التعرُّف على أحوال المجتمع، نظرًا لما تثيره من انتعاش لمسألة الانغماس في عقيدة الولاية الرُّوحية في الأوساط الاجتماعية، مؤكِّدة سبق المستشرقين الأروبيين؛ من مؤرِّخبن وأنثروبولوجيين وميثولوجيين وسوسيولوجيين، إلى الاهتمام بأدب المناقب في العصر الحديث، في سياق البحث عن جذور المعتقدات الشّعبية للمغاربة، وأسباب تقديسهم لأضرحة الأولياء ولرباطاتهم، وما استتبع ذلك من ظهور مجموعة من المنغرافيات والدِّراسات الفرنسية حول المعتقدات الدِّينية بالمغرب، فضلاً عن انفتاح مجموعة من الدِراسات الموظِّفة للأدب المنقبي كالسِّيميائيات والأنثروبولوجيا، مما دفع بالمدرسة المغاربية التاريخية الحديثة إلى الاهتمام والانكباب حول كتب المناقب دراسة وتحقيقًا. ولعلّ المراهنة على مصنّف « ربح التِّجارة ومغنم السّعادة فيما يتعلّق بأحكام الزِّيارة »، لمؤلِّفه الحاج موسى علي بن أحمد الجزائري ( ت حوالي 1330هـ / 1911م )، إحدى المصنّفات المناقبية التي يتوفّر عليها تراث الجزائر خلال القرن: 19م(2)، ومحاولة تفكيك نصوصه المعتمدة، كفيلٌ لتبيُّن تمثُّلاته الواقعية ( الزّمكانية ) في مجال يعكس أبعاد النص المناقبي كحقل خبري له أهميته في كتابة التّاريخ الاقتصادي والاجتماعي والفكري لبلاد المغرب خلال العصر الحديث، ويعكس هموم وقضايا فئات اجتماعية اتّخذت من الزُّهد والنُّسك والتصوُّف منهجًا في الحياة، ويؤكِّد على تقديم خطابه الصُّوفي من أجل تجربته وجعله واقعًا ملموسًا من خلال سلوك المتصوِّفة المترجَمِ لهم وسيرتهم، وسلاسل أنسابهم كغاية لوجودها، ثم انتشارها كشكل تعبيري بخاصِّيات منقبية متفرِّدة، للانتقال من مستوى النّظرية إلى مستوى الصُّورة الحقيقة المرئية للتصوُّف. فهل يمكن الاعتماد على هذا المصنّف في فهم أدبيات الفكر الصُّوفي ورسم صورته من خلال أخبار مشحونة بالكرامات السّاذجة؟ ذلك أنّ النص المناقبي بعد القرن: 13هـ / 19م، أبان عن قصوره على محاكاة الكرامة في علاقة القدسي بالمتخيِّل، وقد تجلّى ذلك في المنحى الذي أخذته الطّريقة الرّاشدية في تصوُّف أحمد بن يوسف الملياني الرّاشدي ( ت 931هـ / 1524م )، وهل يمكن الاعتماد على منهج التأويل في التأريخ للواقعة التاريخية التي عاصرها الأثر المنقبي في عصره الوسيط برواية منقبية حديثة الطّرح زمكانيًا؟ أم أنّ هذا النص نسقٌ من أنساق التُّراث الثقافي الشّعبي الذي أنتجه الأدب الصُّوفي مع مطلع القرن:19م؟ abstract The Literary and historical studies point to the importance of morality manuscripts to identify the conditions of society, Due to the raised questions about the interaction of its various components and events. It has had an impact in the recovery of the issue of spiritual jurisdiction in the Bedouin communities and urban, , as sacred religious concept imposes itself strongly substitute for temporal power. Able to show its realistic similarities in a particular field reflect the dimension of the virtue text as Narrative style has its importance in the writing of the economical,, social and intellectual history of wester nation during the modern era,and reflect the problems and issues of certain categories that has taken Narrative style has its importance in the writing of the economical,, social and intellectual history of wester nation during the modern era,and reflect the problems and issues of certain categories that has taken Abnegation, asceticism and mysticism as lifestyle,And he confirms to deliver his speech to the mystic experience and make it a reality through the conduct of Sufis Translator for them and their careers, andChains of their genealogies as an end to its existence, and then spread as a form expressive with features individually, to move from the level of theory to real visual image of Sufism. To what extent can rely on historian of virtues in highlighting the history mechanism in virtue text? Can we bet on<< profit trade>> in the understanding of the literature of the Sufi thought and drawing its image through a overloaded news silly dignities? The Literary and historical studies point to the importance of morality manuscripts to identify the conditions of society, Due to the raised questions about the interaction of its various components and events. It has had an impact in the recovery of the issue of spiritual jurisdiction in the Bedouin communities and urban, , as sacred religious concept imposes itself strongly substitute for temporal power.Able to show its realistic similarities in a particular field reflect the dimension of the virtue text as Narrative style has its importance in the writing of the economical,, social and intellectual history of wester nation during the modern era,and reflect the problems and issues of certain categories that has taken Narrative style has its importance in the writing of the economical,, social and intellectual history of wester nation during the modern era,and reflect the problems and issues of certain categories that has taken Abnegation, asceticism and mysticism as lifestyle,And he confirms to deliver his speech to the mystic experience and make it a reality through the conduct of Sufis Translator for them and their careers, , andChains of their genealogies as an end to its existence, and then spread as a form expressive with features individually, to move from the level of theory to real visual image of Sufism.To what extent can rely on historian of virtues in highlighting the history mechanism in virtue text? and Can we bet on<< profit trade>> in the understanding of the literature of the Sufi thought and drawing its image through a overloaded news silly dignities?
مقال
Keywords: التُّراث الجزائري